The “Lasso Sign”: An Early Sonographic Sign of Posterior Meningocele - Weissmann-Brenner, Alina (International Scholarly Research Network, 2011)
Posterior meningocele is an uncommon form of spina bifida. We present a case of unique posterior meningocele diagnosed at the early second trimester anatomical scan using 2D and 3D ultrasound. The sonographic appearance resembled “lasso”. The prenatal follow-up was uneventful, with no demonstration of tethered cord. Clinical, neurological and radiological examinations following delivery and at the age of four months were unremarkable.